THE ANALYSIS OF ORNAMENT FORM OF ARAB TOWN AL-MUNAWWAR TRADITIONAL HOUSE - Mukhsin Patriansah; Yayan Hariansyah (LPPMPP Institut Seni Indonesia Padangpanjang, 2019)
The people of Arab town Al-Munawwar in Palembang city use ornament to add aesthetic value of their residential buildings. The use of this ornament can be seen from several sides such as door, window, ventilation, wall, partition, pole, and so on. It's also possible that there are messages and meanings that are interesting to be studied from the ornament of Arab town Al-Munawwar traditional house. The study in this research emphasized more on aesthetic value, with the purpose of searching the structure that built and revealing the symbolic value implied in the traditional house ornament of Arab town Al-Munawwar Palembang. Research method used was qualitative method, with analytic descriptive analysis. Those data were then identified, classified, selected, analyzed, and interpreted according to their text and context.